Analysis of The Strengths and Weaknesses of Burai Tourism Village in Ogan Ilir Regency - L. Prima; F. Amalia; A. Ulfa; M. N. Berlian; F. A. Prayoga Aziz; N. Rahmadhino (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2024)
Burai Village, situated in Tanjung Batu District, Ogan Ilir Regency, South Sumatra Province, has been classified as a tourist village since 2018. The village's economy, which heavily depends on tourism, has been adversely affected by the Covid-19 pandemic. This situation has hindered the village's ability to utilise its significant potential fully. The objective of the research is to analyse the strengths and weaknesses of the village, serving as a foundation for exploring its potential for development. The research utilises qualitative methods, interviews, and SWOT analysis. The findings from this analysis can be used to maximise the tourism potential in Burai Village and other tourist villages across Indonesia. Ultimately, the goal is to uncover and revitalise Burai Village's potential as a tourist destination.